Lenvatinib in Advanced Radioiodine-Refractory Thyroid Cancer - A Retrospective Analysis of the Swiss Lenvatinib Named Patient Program - Balmelli, Catharina (J Cancer, 2018)
Purpose:Differentiated thyroid cancer (DTC) accounts for approximately 95% of thyroid carcinomas. In the metastatic RAI-refractory disease, chemotherapy has very limited efficacy and is associated with substantial toxicity. With increasing knowledge of the molecular pathogenesis of DTC, novel targeted therapies have been developed. Lenvatinib is a tyrosine kinase inhibitor (TKI) with promising clinical activity based on the randomized phase III SELECT trial. In Switzerland, a Named Patient Program (NPP) was installed to bridge the time gap to Swissmedic approval. Here, we report the results from the Swiss Lenvatinib NPP including patients with metastatic RAI-refractory DTC. Methods:Main inclusion criteria for the Swiss NPP were RAI-refractory DTC, documented disease progression, Eastern Cooperative Oncology Group (ECOG) performance status 0-3. The number of previous therapies was not limited. The Swiss Lenvatinib NPP was initiated in June 2014 and was closed in October 2015 with the approval of the drug. Results:Between June 2014 and October 2015, 13 patients with a median age of 72 years have been enrolled. Most patients (69%) had at least one prior systemic therapy, mainly sorafenib. 31% of patients showed a PR and 31% SD. Median progression free survival was 7.2 months and the median overall survival was 22.7 months. Dose reduction due to adverse events was necessary in 7 patients (53%). At the time of analysis 6 patients (47%) were still on treatment with a median time on treatment of 9.98 months. Conclusions:Our results show that lenvatinib has reasonable clinical activity in unselected patients with RAI-refractory thyroid cancer with nearly two-third of patients showing clinical benefit. The toxicity profile of lenvatinib is manageable.